2010
DOI: 10.1177/001979391006300209
|View full text |Cite
|
Sign up to set email alerts
|

Workers' Compensation: Recent Developments in Moral Hazard and Benefit Payments

Abstract: Studies using pre-1990 data generally found benefit and frequency elasticities for workers' compensation cash benefits that exceeded, respectively, 1.0 and 0: an increase in expected benefits apparently induced (a) an even greater increase in actual benefit payments and (b) an increase in claim frequency. Researchers previously hypothesized that incentive effects for workers dominated those for employers. The authors of this study reevaluate benefit and frequency elasticities for 1975–89, using data with some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…In states passing these reforms, they accounted for 12.2-23.7% of the decline. Guo and Burton [2010] identified several factors that help explain the decline in cash benefits in many states during the 1990s. They constructed a measure for the benefit allowance stringency (the BAS variable), which looked at the proportion of injuries reported by employers to OSHA that resulted in workers' compensation claims, and found that the proportion declined between 1985 and 1999 as state workers' compensation programs became more stringent because of administrative practices, rules, or decisions by state agencies or courts.…”
Section: Procedural Hurdlesmentioning
confidence: 99%
“…In states passing these reforms, they accounted for 12.2-23.7% of the decline. Guo and Burton [2010] identified several factors that help explain the decline in cash benefits in many states during the 1990s. They constructed a measure for the benefit allowance stringency (the BAS variable), which looked at the proportion of injuries reported by employers to OSHA that resulted in workers' compensation claims, and found that the proportion declined between 1985 and 1999 as state workers' compensation programs became more stringent because of administrative practices, rules, or decisions by state agencies or courts.…”
Section: Procedural Hurdlesmentioning
confidence: 99%
“…Thus, the workers' compensation moral hazard story is a complicated one that involves much more than worker claiming patterns (Baker 1996). Confirming this conclusion, Guo & Burton (2010) find that "much of the substantial decline in actual benefits in the 1990s was due to changes in state compensability rules and administrative stringency," rather than to worker behavior. …”
Section: Moral Hazard In Workers Compensation Insurancementioning
confidence: 85%
“…44 This may be because moral hazard is less of an issue for the more serious, permanent injuries, or because labor supply disincentives in WC are smaller than previously estimated (Bronchetti and McInerney (2009); Guo and Burton (2010)). This result may also arise merely because with so many regressions estimated, some relationships may be statistically significant by chance (see, e.g., Bland and Altman (1995)).…”
Section: The Effect Of Workers' Compensation Program Parameters On Womentioning
confidence: 99%
“…Following the WC literature, we first consider a tightening in WC parameters (see, e.g., Bronchetti and McInerney (2009);Guo and Burton (2010); Guo and Burton (under review); Guo and…”
Section: Workers' Compensation Policy Changesmentioning
confidence: 99%
See 1 more Smart Citation